PHYSICAL AND CHEMICAL TESTS OF CANDLENUT (Aleurites moluccanus) DRIED AT VARIOUS OVEN TEMPERATURES - Yusnia Afriana; Devi Tanggasari (Protech Biosystems Journal, 2025)
: The characteristics of dried candlenut are largely determined by temperature variations during drying. The purpose of this study was to determine the effect of variations in drying temperature on the fat content, protein content, and weight loss of candlenut (Aleurites moluccanus) seeds. Drying was carried out using an oven with three temperature variations, namely 40°C, 55°C, and 70°C. The parameters analyzed in this study included weight loss, water content, fat content, and protein content as indicators of quality and drying efficiency. The experimental design in this study used a Completely Randomized Design (CRD). The results showed that increasing the drying temperature significantly affected the fat content and weight loss. A temperature of 70°C produced the highest fat content of 67.64%, while a temperature of 40°C showed the lowest content of 60.96%. In addition, the higher the drying temperature, the greater the level of weight loss that occurs due to faster and more effective water evaporation. Protein content also experienced changes, although not significant, but tended to be stable at medium to high drying temperatures. Based on these results, it can be concluded that a drying temperature of 70°C is the optimal temperature for increasing the fat content and drying efficiency of candlenuts without significantly reducing the protein content.